A High‐Voltage Molecular‐Engineered Organic Sensitizer–Iron Redox Shuttle Pair: 1.4 V DSSC and 3.3 V SSM‐DSSC Devices. Issue 19 (6th April 2018) - Rodrigues, Roberta R.; Cheema, Hammad; Delcamp, Jared H.
Abstract: The development of high voltage solar cells is an attractive way to use sunlight for solar‐to‐fuel devices, multijunction solar‐to‐electric systems, and to power limited‐area consumer electronics. By designing a low‐oxidation‐potential organic dye (RR9 )/redox shuttle (Fe(bpy)3 3+/2+ ) pair for dye‐sensitized solar‐cell (DSSC) devices, the highest single device photovoltage (1.42 V) has been realized for a DSSC not relying on doped TiO2 . Additionally, Fe(bpy)3 3+/2+ offers a robust, readily tunable ligand platform for redox potential tuning.RR9 can be regenerated with a low driving force (190 mV), and by utilizing theRR9 /Fe(bpy)3 3+/2+ redox shuttle pair in a subcell for a sequential series multijunction (SSM)‐DSSC system, one of the highest known three subcell photovoltage was attained for any solar‐cell technology (3.34 V, >1.0 V per subcell). Abstract : Record photovoltages are obtainable for single‐junction DSSC devices and three subcell SSM‐DSSC systems through the judicious, simultaneous energy‐level tuning of a novel organic sensitizer and redox shuttle. Tuning both the dye ground‐state and redox shuttle potential provides a unique direction to maximize photovoltage output from high‐energy photons.